2021
DOI: 10.1038/s41598-021-83267-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome reveals mechanisms underlying Rlm1-mediated blackleg resistance on canola

Abstract: Genetic resistance to blackleg (Leptosphaeria maculans, Lm) of canola (Brassica napus, Bn) has been extensively studied, but the mechanisms underlying the host–pathogen interaction are still not well understood. Here, a comparative transcriptome analysis was performed on a resistant doubled haploid Bn line carrying the resistance gene Rlm1 following inoculation with a virulent (avrLm1) or avirulent (AvrLm1) Lm isolate on cotyledons. A total of 6999 and 3015 differentially expressed genes (DEGs) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…It has been shown that climate changes, such as variation in the CO 2 concentration, temperature fluctuations and water availability, play a role in influencing disease outcomes in host plants [61]. Disease severity is also impacted by the type of disease resistance of the host, whether it is qualitative or quantitative; in Brassica blackleg disease [62][63][64][65][66][67][68], or in the qualitative type, it depends on the specific pathotype that infects the host. For example, in the B. napus-Pyrenopeziza brassicae (light leaf spot) interaction, the host resistance is specific to the isolated pathotypes [69].…”
Section: Complex Host-pathogen Interactionmentioning
confidence: 99%
“…It has been shown that climate changes, such as variation in the CO 2 concentration, temperature fluctuations and water availability, play a role in influencing disease outcomes in host plants [61]. Disease severity is also impacted by the type of disease resistance of the host, whether it is qualitative or quantitative; in Brassica blackleg disease [62][63][64][65][66][67][68], or in the qualitative type, it depends on the specific pathotype that infects the host. For example, in the B. napus-Pyrenopeziza brassicae (light leaf spot) interaction, the host resistance is specific to the isolated pathotypes [69].…”
Section: Complex Host-pathogen Interactionmentioning
confidence: 99%
“…Canola ( Brassica napus L.) is the number one cash crop in Canada, contributing CAD 29.9 billion to the national economy annually, including more than 207,000 Canadian jobs and CAD 12 billion in wages [ 1 ]. Annual global and Canadian canola production is estimated as 70 MMT and 18.7 MMT, respectively [ 1 , 2 ]. Blackleg, caused by the actinomycete fungus Leptosphaeria maculans (Desm.)…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, the RNA-seq technique has been widely used to investigate plant pathosystems, including the canola-blackleg system. Several studies have been studied the host system [ 2 , 9 ] and pathogen system [ 48 ] separately. In addition, there were few studies have been studied the whole host-pathosystem by dual RNAseq as well [ 49 ].…”
Section: Introductionmentioning
confidence: 99%